Tacrolimus modulates the PI3K AKT mTOR pathway in retinal epithelial cells under inflammatory stress - Kiełbasińska, Aleksandra; Grabarek, Beniamin Oskar; Janiszewska-Bil, Dominika; Machaj, Martyna; Lelek, Zuzanna; Boroń, Anita Lyssek; Koss, Michael Janusz; Waszak, Jacek; Krysik, Katarzyna (Scientific reports, 2025)
Human retinal pigment epithelial (H-RPE) cells contribute to the pathogenesis of proliferative vitreoretinopathy (PVR) by undergoing inflammatory activation and fibrotic transformation. The PI3K/AKT/mTOR signaling pathway plays a central role in this process, integrating extracellular cues that promote survival, proliferation, and matrix remodeling. Tacrolimus, a calcineurin inhibitor with emerging antifibrotic properties, may modulate these responses at both transcriptional and post-transcriptional levels. H-RPE cells were treated with lipopolysaccharide (LPS), tacrolimus, or their combination to simulate inflammatory and immunosuppressive conditions. Transcriptomic profiling was performed using microarrays, followed by RT-qPCR and ELISA validation of selected targets. A parallel analysis of microRNAs (miRNAs) was conducted to assess potential regulatory interactions. Protein-protein interaction (PPI) networks were generated using the STRING database. Microarray analysis identified 38 PI3K/AKT/mTOR-associated mRNAs with significant differential expression (|FC| > 4.0, p < 0.05), including CDK2, PIK3CA, STAT3, MTOR, and COL1A1. LPS treatment led to strong upregulation of inflammatory and fibrotic genes, while tacrolimus reversed or attenuated many of these effects. miRNA profiling revealed inverse regulation of several transcripts by hsa-miR-27a-5p, miR-29a-3p, and miR-1271-5p. Protein measurements confirmed these trends, and STRING analysis highlighted a densely connected network with central nodes including JAK1, EGFR, and MTOR. This study supports the therapeutic potential of tacrolimus in retinal fibrosis by demonstrating its ability to modulate the PI3K/AKT/mTOR-miRNA axis in inflamed H-RPE cells, suppress key fibrotic and proliferative genes, and restore regulatory microRNA expression, offering a promising strategy for controlling H-RPE-driven remodeling PVR.
Gesehen am 27.02.2026